Innovate emergency governance mechanism of urban communities in response to major public health events: A qualitative study from multiple principals in Guangzhou, China - Liting Zhou; Fei Ouyang (Frontiers Media S.A., 2023)
Since the end of 2019, the sudden outbreak of COVID-19 has challenged the emergency governance systems of various countries. As the cornerstone of national governance, China's community emergency governance mainly adopts top-down organizational mobilization and rapid response, which is typical abnormal governance. In responding to major public health events, China's national system has developed certain advantages in some respects. However, the current pandemic is still serious in many places, and new mutant strains are constantly appearing. Some drawbacks of such system and mechanism are gradually emerging. In the process of preventing and controlling the pandemic, China's urban communities have continuously improved the joint mechanism, and played the role of multiple principals in collaborative and co-governance. The current work of pandemic prevention and control has entered a period of normalization. What is the collaborative mechanism of multiple principals (Subdistrict headquarter, Community committee, Owners' committee, Community hospital, Local police station, Property management company, etc.) in urban communities participating in emergencies and how to seek ways to further improve the mechanism? Therefore, taking the community practice and actions in Guangzhou, China as an example, the present study employed a qualitative design, proposed to better community emergency governance mechanisms from the aspects of preparedness, response, communication and recovery, so as to provide a reference for other grassroots organizations.